TANTANGAN DAN PROSPEK SISTEM BASIS DATADALAM PENDIDIKAN ISLAM - Padlianor, Padlianor; Ramadani, Wahdatul; Hermina, Dina (PT. Hasba Edukasi Mandiri, 2026)
Advancements in Information and Communication Technology (ICT) necessitate that Islamic educational institutions adopt database systems to enhance management quality, instructional effectiveness, and data-driven decision-making. This study aims to analyze the challenges and prospects surrounding the implementation of database systems within Islamic education, particularly in the era of digital transformation and the integration of Artificial Intelligence (AI). The analysis indicates that the implementation of database systems across Islamic educational sectors encompassing State Islamic Higher Education Institutions (PTKIN), madrasahs, and Islamic boarding schools (pesantren) remains varied and in a transitional phase. Implementation is currently hindered by siloed systems, infrastructure gaps, and limited digital literacy. However, AI integration offers profound prospects for personalized learning and operational efficiency. Ultimately, anchoring these systems in Islamic ethics and maqāshid al-syarī’ah is essential for fostering a modern, competitive educational ecosystem